Stauroneis lacusvulcani sp. nov. (Bacillariophyceae), a new diatom from volcanic lakes in northeastern China - Rioual, Patrick; Gao, Qiang; Peng, Yumei; Chu, Guoqiang (Phytotaxa, 2013)
Stauroneis lacusvulcani sp. nov. is described from two small volcanic lakes in northeastern China. The morphology of S. lacusvulcani is illustrated with light and scanning electron micrographs and discussed in comparison with several species of the Stauroneis gracilior group. S. lacusvulcani can be distinguished by the size of the valves and its long-protracted and strongly capitate apices. Diatom analysis of the sedimentary record from Lake Xiaolongwan (Jilin Province) showed that this new species was most abundant during the early Holocene ( 8950 to 10,640 yrs BP).